2014
DOI: 10.1016/s1473-3099(14)70845-x
|View full text |Cite
|
Sign up to set email alerts
|

Safety and immunogenicity of a candidate tuberculosis vaccine MVA85A delivered by aerosol in BCG-vaccinated healthy adults: a phase 1, double-blind, randomised controlled trial

Abstract: SummaryBackgroundIntradermal MVA85A, a candidate vaccine against tuberculosis, induces high amounts of Ag85A-specific CD4 T cells in adults who have already received the BCG vaccine, but aerosol delivery of this vaccine might offer immunological and logistical advantages. We did a phase 1 double-blind trial to compare the safety and immunogenicity of aerosol-administered and intradermally administered MVA85AMethodsIn this phase 1, double-blind, proof-of-concept trial, 24 eligible BCG-vaccinated healthy UK adul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
138
0
2

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 159 publications
(154 citation statements)
references
References 28 publications
13
138
0
2
Order By: Relevance
“…Recent studies have shown that a subunit vaccine can be delivered safely to the lung using an aerosol delivery device in both nonhuman primates and humans Although these studies were performed with MVA85A, the proof-of-concept safety and immunogenicity data generated from this study [94,95] will accelerate the clinical testing of aerosol vaccines emerging from the TBVAC2020 and EMI-TB consortiums.…”
Section: Carbapenem-clavulanic Acidmentioning
confidence: 99%
“…Recent studies have shown that a subunit vaccine can be delivered safely to the lung using an aerosol delivery device in both nonhuman primates and humans Although these studies were performed with MVA85A, the proof-of-concept safety and immunogenicity data generated from this study [94,95] will accelerate the clinical testing of aerosol vaccines emerging from the TBVAC2020 and EMI-TB consortiums.…”
Section: Carbapenem-clavulanic Acidmentioning
confidence: 99%
“…MVAAg85A represents one of the most advanced TB vaccine candidates to date. Although the recent phase IIb efficacy trial in South Africa demonstrated that the parenteral route of boosting was ineffective in enhancing protection in BCG-primed infants [9], the demonstrated safety and immunogenicity in a recent phase I MVAAg85A aerosol trial has provided the rationale, and optimism, for respiratory mucosal delivery of a TB vaccine in humans [35].…”
Section: Respiratory Mucosal Vaccination In Human Clinical Trialsmentioning
confidence: 99%
“…We have just published results from a Phase I clinical trial comparing the safety and immunogenicity of the MV85A vaccine, delivered either by a needle or an aerosol, in individuals who had previously been vaccinated with BCG. 7 This was a very successful study as it showed that the aerosol delivery was safe and also generated stronger immune responses in the lungs than the conventional delivery of the vaccine using a needle. As well as stimulating superior immune responses in the lungs, the aerosol delivery method also had comparable, if not trending toward higher, immune responses in the blood than the needle delivery method.…”
Section: From Aids To Tb Vaccines -A Career In Infectious Diseases Anmentioning
confidence: 99%